Physical Activity and Ischemic Stroke Prevention - Gabriela Ferfecka; Patrycja Marta; Klaudia Pawełek; Natalia Morawiecka; Magdalena Rosa-Bończak; Agata Ossolińska; Filip Huzarski; Lucyna Stolarska; Weronika Kłosowicz; Olivier Carlton (Journal of Education, Health and Sport)
Introduction: Ischemic stroke is one of the most common cerebrovascular diseases, a leading cause of disability, and the primary cause of death globally. Numerous risk factors for stroke can be eliminated or mitigated through proper health-promoting measures, with regular physical activity being one of the most crucial. Exercise directly and indirectly reduces stroke risk by enhancing cardiovascular health and mitigating other risk factors.